Socio-demographic factors as predictors on types of productive aging among retirees in the Klang Valley, Malaysia - Adnan, Aziera Adleen (2021)
The aim of this study is to predict the likelihood of socio-demographic factors on type of productive time use activities among UPM’s retirees. This study intends to bridge the gap in literature by analyzing the likelihood of socio-demographic factors on type of productive aging based on time use pattern. Specifically, this study was conducted with the aim of achieving four objectives namely i) to determine the pattern of time use among UPM’s retirees; ii) to determine productive activities categories among UPM’s retirees based on time use pattern; iii) to determine the prediction of socio-demographic factors on types of productive aging among UPM’s retirees; and iv) to estimate the economic value of productive activities of UPM’s retirees. Despite the aging population has become one of the most critical socio-demographic phenomena across the world, few empirical studies have been conducted to investigate the literature through the estimations of the economic value of older person’s contribution to the society and profiling them with types of productive aging through the pattern of their time use. Thus, two main approaches have been used to value unpaid work namely: i) replacement cost, and ii) opportunity cost. Literatures generally focuses on seeing older person as burden to society. Therefore, the estimation cost from both methods have been used to differentiate the economic gap between the economic contributions produced by older people and the pension costs provided by the government that has been received to the older people. A total of 210 respondents participated in the study. A multinomial logistic regression was performed to model the relationship between the socio-demographic factors (gender, age, education level, marital status, employment status, income level) and membership in the four groups (labor force type, household management activities, care/support activity and self-management type). Results indicated that time use pattern associated with type of productive aging among older people were different based on socio-demographic factors. The probability of older adults belonging to a certain cluster was significantly different by gender, education level, marital status, employment status and income level. This helps to explain what kinds of attributes construct differentials in older adulthood, via which types of productive activities. In conclusion, older people may be thought to be inactive when they may actually be producing much more than we commonly expect. Thus, this undoubtedly requires a sharing of responsibilities between the government, private sector, non-governmental agencies and the community to understand the potential roles of the older adults as active community members and aim at promoting productive aging in future.